Analisis Kadar Glukomanan Dari Biji Durian (Durio zeibethinus Murr) dengan Metode Spektrofotometri pada Berbagai Waktu dan Suhu Hidrolisis: Analysis of Glucomannan Content From Durian Seeds (Durio zeibethinus Murr) Using Spectrophotometry Methods in Several Hydrolysis Times and Temperatures - Darmawati Darmawati; Syaiful Bahri; Husain Sosidi (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2020)
Durian seeds are one type of seed that contains glucomannan. The aim is to determine glucomannan levels in the durian seed. The study was designed using a completely randomized design (CRD). The extracted glucomannan was determined by the spectrophotometry method at various temperature and hydrolysis time. The crude extract of glucomannan was hydrolyzed using 3 M HCl for 70, 80, 90, 100, and 110 minutes at 70, 80, 90, 100, and 110°C. The highest glucomannan concentration of 39.60% was obtained at a hydrolysis temperature of 100°C for 100 minutes. The analysis of the FTIR spectrophotometer shown that the vibration of the C-O-C functional group (glycoside bond) was obtained at the wavelength number of 1020.34 cm-1 which is a characteristic of glucomannan. Keywords: glucomannan, durian seed, hydrolysis, spectrophotometry